Review on vibration control in tall buildings: from the perspective of devices and applications - Kavyashree, BG; Patil, Shantharam; Rao, Vidya S. (International journal of dynamics and control, 2021)
Permanent construction has evolved from the Palaeolithic age to today’s skyscrapers. Constructing the structure, which promises occupants safety, has become a concern because of the uncertainties in nature. Therefore in recent years, attention has been given to the development of structural protective devices that could take care of the external loads. Structural control against the wind and earthquake load has been seriously studied where the structure behaves differently for wind and earthquake load has been briefly discussed in this paper. Initially, paper discusses the history of the construction and the passive control system, which was used in structural control, is briefly discussed in this paper. Also, the implementation of active control has been discussed which was introduced later in the structural control for more effective control. But the limitations of the passive and active control system have introduced semi-active control and also the hybrid control strategy. The two mechanisms are put together in the semi-active and hybrid system to obtain all advantages of the algorithm along with overcoming their limitations. The review also briefs about stochastic vibrational control of the structure where randomness is considered in external loads, parameter of the system and also in the external devices which are implemented in the structural control. As construction sector is a complex system, big data analysis, a new field in structural control system is discussed and future scope is also mentioned.